2022
DOI: 10.1061/(asce)gt.1943-5606.0002817
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge Model Tests of Liquefaction-Induced Downdrag on Piles in Uniform Liquefiable Deposits

Abstract: Earthquake-induced soil liquefaction can cause settlement around piles, which can translate to negative skin friction and the development of drag load and settlement of the piles. A series of centrifuge model tests were performed to assess liquefaction-induced downdrag and understand the interplay and effects of (1) pile embedment and pile-head load, (2) excess pore pressure generation and dissipation, and (3) reconsolidation and ground settlement on pile response during and postshaking. The model included a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Fleming et al (2008) showed that displacements of 0.5% to 2% of pile diameter are required to mobilize the shaft capacity. Sinha et al (2022b) performed a series of centrifuge model tests and found that soil displacements of 1%-3% of the pile's diameter were sufficient to mobilize the total skin friction capacity. The nonlinear backbone curve for t-z material (Boulanger et al 1999;Mosher 1984;Reese and O'Niel 1987) is a hyperbolic curve that takes displacement equal to about four times z 50 to mobilize >90% of the ultimate capacity (t o ult ).…”
Section: Boulangermentioning
confidence: 99%
See 4 more Smart Citations
“…Fleming et al (2008) showed that displacements of 0.5% to 2% of pile diameter are required to mobilize the shaft capacity. Sinha et al (2022b) performed a series of centrifuge model tests and found that soil displacements of 1%-3% of the pile's diameter were sufficient to mobilize the total skin friction capacity. The nonlinear backbone curve for t-z material (Boulanger et al 1999;Mosher 1984;Reese and O'Niel 1987) is a hyperbolic curve that takes displacement equal to about four times z 50 to mobilize >90% of the ultimate capacity (t o ult ).…”
Section: Boulangermentioning
confidence: 99%
“…The piles were instrumented with strain gauges in full-bridge configuration inside the pipe to measure the axial load distribution. The interface was made significantly rough to achieve full interface friction angle (δ ¼ 30°) (Sinha et al 2022b). The 0D, 3D, and 5D naming annotations indicate the embedment depth of the pile tip; that is, the 0DPile had its tip placed at the bottom of the loose sand layer, whereas the 3D and 5D piles had their tips embedded 3 and 5 times their diameter into the dense sand.…”
Section: Description Of Centrifuge Model Testsmentioning
confidence: 99%
See 3 more Smart Citations